Root associated fungi in Arctic Glacier Forlands raw sequences ... - Eidesen, Pernille Bronken; Botnen, Synnøve S.; Mundra, Sunil; Kauserud, Håvard (Dryad, 2020)
Climate change causes Arctic glaciers to retreat faster, exposing new areas for colonization. Several pioneer plants likely to colonize recent deglaciated, nutrient-poor areas depend on fungal partners for successful establishment. Little is known about general patterns or characteristics of facilitating fungal pioneers and how they vary with regional climate in the Arctic. The High Arctic Archipelago Svalbard represents an excellent study system to address these questions, as glaciers cover ∼60% of the land surface and recent estimations suggest at least 7% reduction of glacier area since 1960s. Roots of two ectomycorrhizal (ECM) plants (Salix polaris and Bistorta vivipara ) were sampled in eight glacier forelands. Associated ECM fungi were assessed using DNA metabarcoding. About 25% of the diversity was unknown at family level, indicating presence of undescribed species. Seven genera dominated based on richness and abundance, but their relative importance varied with local factors. The genus Geopora showed ... : DNA was extracted from the entire plant root system using a modified CTAB extraction protocol , and further purified using the E.Z.N.A. Soil DNA kit (Omega Bio-tek, USA) following the manufacturer's protocol. A negative control was used during extraction procedure and included in PCR and sequencing. We amplified the internal transcribed space 2 (ITS2) region of the nuclear ribosomal rDNA using primers fITS7a and ITS4. PCR procedures, library preparation and Multiplex Identification DNA-tags. Paired-end sequencing (2 × 300) was performed on an Illumina MiSeq sequencer ...